Zeleno zavajanje v športnem turizmu - Buzina, Lara (Pravni letopis, 2025)
Sports tourism accounts for about one-tenth of global tourism spending and is one of the fastest-growing sub-sectors of the global tourism industry. However, the growth of sports tourism also brings increased environmental and social impacts, which is why the importance of sustainable development is becoming increasingly recognised. As consumers expect clear and credible information about the sustainable practices of sports event organisers, greenwashing, i.e. the exaggerated or untruthful presentation of sustainable achievements, is becoming a serious problem. Such practices lead to a loss of consumer confidence, the emergence of green scepticism and reduce the impact of genuine sustainability efforts. As a sports and tourism destination, Slovenia has the opportunity to consolidate its competitive advantage and contribute to the long-term protection of the environment on which this industry is based by consistently implementing verifiable sustainability measures as defined in the proposed Green Claims Directive.
Keywords: competitiveness; consumers; European Union; Evropska unija; green claims; greenwashing; konkurenčnost; potrošniki; sports tourism; sustainable development; Šport in trajnostni razvoj; Šport in turizem; športni turizem; trajnostni razvoj; Varstvo okolja; Varstvo potrošnikov; zelene trditve; zeleno zavajanje